Implementation of An Integrated Information System In Early Childhood Education Schools In Teacher Administrative Management - Revita Yanuarsari; Susan Maulani; Tedi Hadiana; Nur Indah Juniati (Jurnal Isema : Islamic Educational Management, 2024)
PAUD (Early Childhood Education) schools have an important role in establishing the foundations of education at an early age. Efficient and timely administrative management is needed to ensure the school's daily operations run smoothly. In an effort to improve teacher administrative management, the use of an Integrated Information System (PAUD SITE) was proposed as a potential solution. This system will integrate various administrative aspects, such as managing schedules, attendance, teacher personal data, announcements, and communication between the teacher and the school. This research involves an in-depth analysis of how the implementation of the PAUD SITE can affect the efficiency and effectiveness of teacher administrative management. The research method used is a qualitative approach. Data was collected through interviews with school administrative staff and teachers, as well as a survey given to teachers and related schools. The results of this study are expected to provide a better understanding of the benefits and challenges associated with the implementation of the PAUD SITE in teacher administration management in PAUD schools. The practical implications of this research can be used as a guide for PAUD schools wishing to introduce or increase the use of an integrated information system in their daily operations.